1995
DOI: 10.1111/j.1540-8167.1995.tb00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Sensitivity

Abstract: Baroreflex sensitivity (BRS) has rapidly gained considerable attention as a result of multiple experimental and clinical reports on its prognostic value after a myocardial infarction. This article reviews the several aspects related to the use and significance of BRS. The methodology of baroreflex testing in man is described. The complex pathophysiology underlying BRS and the hypotheses proposed to explain its frequent reduction after a myocardial infarction are discussed. The section on experimental data also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 69 publications
3
57
0
3
Order By: Relevance
“…[21,36] BRS, a well-established index of cardiac vagal responsiveness [37], has been shown to be depressed during sleep in patients with severe OSAS, and uncontrolled short-term trials have suggested an improvement of nocturnal BRS with CPAP treatment [7][8][9]. In the present study, BRS measured during daytime increased by 24% after 4 weeks of therapeutic CPAP, indicating that the beneficial effect of treatment on the cardiac sympatho-vagal balance is not limited to the sleep period.…”
Section: Brssupporting
confidence: 59%
“…[21,36] BRS, a well-established index of cardiac vagal responsiveness [37], has been shown to be depressed during sleep in patients with severe OSAS, and uncontrolled short-term trials have suggested an improvement of nocturnal BRS with CPAP treatment [7][8][9]. In the present study, BRS measured during daytime increased by 24% after 4 weeks of therapeutic CPAP, indicating that the beneficial effect of treatment on the cardiac sympatho-vagal balance is not limited to the sleep period.…”
Section: Brssupporting
confidence: 59%
“…During aging, there is impairment of the baroreflex sensitivity (BRS) for control of heart rate (HR) (13, 15, 32), a marker of parasympathetic tone mediated at the level of the solitary tract nucleus (NTS) in the dorsal medulla (2), due to changes in central neuronal and peripheral vascular function. Importantly, baroreflex dysfunction is permissive to chronic sympathetic activation to increase blood pressure and its variability and is an independent risk factor for cardiovascular morbidity and mortality (25,42). The precise mechanisms involved in agerelated baroreflex impairments, however, are not fully understood.…”
mentioning
confidence: 99%
“…HRT is interrelated with spontaneous BRS and it may be used in its place as a new diagnostic method (27). It is proven that HRT also predicts mortality and sudden cardiac death in various cardiac abnormalities (14,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Increased sympathetic and decreased vagal tone can interact with all of the electrophysiological mechanisms underlying arrhythmogenesis. Efferent cardiac autonomic activity is largely under the control of baroreceptor and BRS, which is correlated with cardiac arrhythmias (29,30).…”
Section: Discussionmentioning
confidence: 99%